Results from a multicenter, noninterventional registry study for multiple myeloma patients who received stem cell mobilization regimens with and without plerixafor - Morris, Curly; Chabannon, Christian; Masszi, Tamas; Russell, Nigel; Nahi, Hareth; Kobbe, Guido; Krejci, Marta; Auner, Holger W; Pohlreich, David; Hayden, Patrick; Basak, Grzegorz W; Lenhoff, Stig; et al. (Bone marrow transplantation, 2020)
Plerixafor plus granulocyte-colony stimulating factor (G-CSF) enhances the mobilization of hematopoietic stem cells (HSCs) for collection and subsequent autologous hematopoietic stem cell transplantation (HSCT) in patients with multiple myeloma (MM). This international, multicenter, noninterventional registry study (NCT01362972), evaluated long-term outcomes for MM patients who received plerixafor versus other mobilization regimens. The comparisons were: G-CSF + plerixafor (G-CSF + P) versus G-CSF-; G-CSF + P versus G-CSF + chemotherapy (G-CSF + C); and G-CSF + P + C versus G-CSF + C. Propensity score matching was used to balance groups. Primary outcome measures were progression free survival (PFS), overall survival (OS), and cumulative incidence of relapse (CIR) after transplantation. After propensity matching, 77 versus 41 patients in the G-CSF + P versus G-CSF cohorts, 129 versus 129 in the G-CSF + P versus G-CSF + C cohorts, and 117 versus 117 in the G-CSF + P + C versus G-CSF + C cohorts were matched, respectively. Propensity score matching resulted in a smaller sample size and imbalances were not completely overcome. For both PFS and OS, the upper limits of the hazard ratio 95% confidence intervals exceeded prespecified boundaries; noninferiority was not demonstrated. CIR rates were higher in the plerixafor cohorts. G-CSF + P remains an option for the mobilization of HSCs in poor mobilizers with MM with no substantial differences in PFS, OS, and CIR in comparison with other regimens.
Keywords: heterocyklické sloučeniny; Heterocyclic Compounds; mnohočetný myelom; registrace; Humans; Multiple Myeloma; benzylaminy; Neoplasm Recurrence, Local; lokální recidiva nádoru; Hematopoietic Stem Cell Mobilization; mobilizace hematopoetických kmenových buněk; Registries; Cyclams; cyklamy; lidé; Benzylamines